2019
DOI: 10.1007/s11618-019-00910-3
|View full text |Cite
|
Sign up to set email alerts
|

Schreibkompetenzen im Fach Englisch in der gymnasialen Oberstufe

Abstract: Zusammenfassung Produktive Sprachkompetenzen im Fach Englisch sind bislang in Deutschland nur wenig untersucht worden. Daher wurden in der vorliegenden Untersuchung mit zwei Messzeitpunkten Kompetenzen im argumentativen und sachorientierten Schreiben von N = 838 Schülerinnen und Schülern in der 11. Jahrgangsstufe Die Daten der vorliegenden Studie stammen aus dem Projekt "Measuring English Writing at Secondary Level (MEWS)", das von der Deutschen Forschungsgemeinschaft (DFG; GZ: KO1513/12-1) und vom Schweizeris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The sample consisted of N = 2,722 upper secondary students (11th grade; 58.1% female) in Germany (n = 894) and Switzerland (n = 1828) from the interdisciplinary and international research project Measuring English Writing at Secondary Level (MEWS; for an overview see Keller et al, 2020). The target population were students attending the academic track of general education grammar schools (ISCED level 3a) in the German federal state Schleswig-Holstein as well as in seven Swiss cantons (Aargau, Basel Stadt, Basel Land, Luzern, St. Gallen, Schwyz, Zurich).…”
Section: Sample and Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…The sample consisted of N = 2,722 upper secondary students (11th grade; 58.1% female) in Germany (n = 894) and Switzerland (n = 1828) from the interdisciplinary and international research project Measuring English Writing at Secondary Level (MEWS; for an overview see Keller et al, 2020). The target population were students attending the academic track of general education grammar schools (ISCED level 3a) in the German federal state Schleswig-Holstein as well as in seven Swiss cantons (Aargau, Basel Stadt, Basel Land, Luzern, St. Gallen, Schwyz, Zurich).…”
Section: Sample and Proceduresmentioning
confidence: 99%
“…In addition to two human ratings per essay, ETS also provided scores from their automated essay scoring system (erater R ; Burstein et al, 2013). For a more detailed description of the scoring procedure and the writing prompts see Rupp et al (2019) and Keller et al (2020). For the purpose of this study, we selected the student responses to the TOEFL iBT independent writing prompt "Teachers, " which showed good measurement qualities (see Rupp et al, 2019).…”
Section: Writing Promptmentioning
confidence: 99%
See 1 more Smart Citation
“…The reliabilities were satisfactory (.80/.81). In Study 2, calibration analyses for English competencies as well as cognitive ability were conducted using Mplus (Version 8.1, Muthén & Muthén, 1998‐2017, as described in Köller et al, 2019; Appendix S1). The reliability was satisfactory, ranging from .72 (T2 listening) to .93 (T1 writing achievement).…”
Section: Methodsmentioning
confidence: 99%
“…The multidimensional modelling of performance in the test of English as a foreign language (TOEFL; Sawaki et al, 2008) shows, in addition to group factors (i.e., reading, listening, speaking, and writing as first‐order factors), a higher‐order factor that expresses performance on the overall test. Köller et al (2019) found reading, listening, and writing to be moderately correlated (approx. r = .50), indicating some variance between the modalities.…”
Section: Introductionmentioning
confidence: 99%